"It Takes a While to Get Used to": The Costs of Redeeming Public Benefits. (4th November 2020) - Barnes, Carolyn Y
Abstract: Scholars have examined how administrative burden creates barriers to accessing public benefits but have primarily focused on the challenges of claiming benefits. Less is known about the difficulties beneficiaries face when using public benefits, especially voucher-based public assistance programs. I argue that the costs of learning how to redeem benefits can discourage program use and undermine policy goals. To enrich the administrative burden framework, this study draws from a qualitative analysis of 43 participants in the Special Supplemental Nutrition Assistance Program for Women, Infants, and Children (WIC) to develop a new subset of learning costs—redemption costs. I argue that two conditions: limited portability and reliance on third-party agents create redemption costs for beneficiaries. I apply these two conditions to two other voucher-based programs: the Housing Choice Voucher Program and the Child Care Subsidy. Examining redemption costs can help clarify when and where beneficiaries experience burdens, reasons behind discontinuity in program participation, and why public programs fail to meet objectives.